THE INFLUENCE OF SERVICE QUALITY AND TRUST ON PATIENT SATISFACTION AT THE KAMONJI COMMUNITY HEALTH CENTER, PALU CITY - Rahmawati; Zahara, Zakiyah; Asngadi (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2024)
The purpose of this study was to determine whether there is an effect of service quality and trust on patient satisfaction at the Kamonji Health Centre either partially or simultaneously. The population is patients or families who come for outpatient treatment at the Kamonji Palu Health Centre. The number of samples used was 100 respondents using the accidental sampling method. The data collection method used a questionnaire. Using causal descriptive analysis, data processing using multiple linear analysis. Based on the t test, service quality has a significant effect on patient satisfaction partially obtained a value of 0.026 <0.05 and trust has a significant effect on patient satisfaction partially with a value of 0.33 <0.05. Simultaneously, service quality and trust affect patient satisfaction based on the F test obtained a value of 0.00 <0.05. From the results of this study, there are still several indicators that get negative ratings from respondents that need special attention from the Kamonji Health Centre, Palu City to further improve the quality of service. be much better.